2000
DOI: 10.1097/00004583-200007000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Early Attention Problems and Children's Reading Achievement: A Longitudinal Investigation

Abstract: Attention problems play an important role in the development of reading difficulties for some children, and screening for attention problems may help identify children at risk for reading difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
202
3
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(237 citation statements)
references
References 13 publications
25
202
3
7
Order By: Relevance
“…For example, in a school sample of 7-16 year olds at baseline, Rapport et al (1999) found that teacher ratings of attention problems and hyperactivity predicted lower academic achievement in reading and mathematics 3 to 4 years later when controlling for both intelligence and teacher rated conduct problems. Similarly, Rabiner et al (2000) found that teacher ratings of attention problems, but not impulsivity-overactivity predicted reading achievement in fifth grade in a school sample, controlling for early reading achievement and intelligence. Fergusson and Horwood (1992) examined the relation between adult ratings of attention problems and academic achievement in children from 10 to 12 years of age.…”
mentioning
confidence: 87%
“…For example, in a school sample of 7-16 year olds at baseline, Rapport et al (1999) found that teacher ratings of attention problems and hyperactivity predicted lower academic achievement in reading and mathematics 3 to 4 years later when controlling for both intelligence and teacher rated conduct problems. Similarly, Rabiner et al (2000) found that teacher ratings of attention problems, but not impulsivity-overactivity predicted reading achievement in fifth grade in a school sample, controlling for early reading achievement and intelligence. Fergusson and Horwood (1992) examined the relation between adult ratings of attention problems and academic achievement in children from 10 to 12 years of age.…”
mentioning
confidence: 87%
“…Dois artigos selecionaram crianças com déficit de atenção e/ou hiperatividade (Rabiner & Coie, 2000;Velting & Grover, 1997) e três artigos selecionaram crianças com problemas de comportamento (Miles & Stipek, 2006;Normandeau & Guay, 1998;.…”
Section: Estudos Sobre Precursores Da Associação Entre Problemas De Cunclassified
“…Quatro artigos iniciam a sua avaliação no jardim da infância (Miles & Stipek, 2006;Normandeau & Guay, 1998;Rabiner & Coie, 2000;Velting & Grover, 1997). Um estudo inicia nos 4-8 meses .…”
Section: Estudos Sobre Precursores Da Associação Entre Problemas De Cunclassified
See 2 more Smart Citations